Bidirectional associations between sensorineural hearing loss and depression and anxiety: a meta-analysis - Zhi-qiang Zhang; Jing-yang Li; Si-tong Ge; Tian-yi Ma; Fu-yao Li; Jun-liang Lu; Shu-rui Si; Zhe-zhu Cui; Yu-lian Jin; Yu-lian Jin; Yu-lian Jin; Xiang-hua Jin (Frontiers Media S.A., 2024)
BackgroundRecently, the prevalence of sensorineural hearing loss (SNL) has been increasing, and several studies have suggested that depression, anxiety, and SNL may be associated with each other, however, individual findings still have discrepancies. To the best of our knowledge, no scholars have systematically elucidated the bidirectional associations between SNL, depression, and anxiety disorders from the perspective of meta-analysis. In this study, we aimed to systematically evaluate the bidirectional associations between SHL and depressive and anxiety symptoms, and to provide evidence-based medical evidence for reducing SNL, depression, and anxiety disorders.MethodsWe performed systematic review based on priori protocol that was registered with PROSPERO (No. CRD42022365963). Systematic search of PubMed, Embase, and Web of Science databases identified articles published as of June 1, 2023, on the relationship between SNL and depression and anxiety. Meta-analysis was performed to calculate the odds ratios (OR) and 95% confidence intervals (CIs) for the outcome metrics, and the results were combined to assess bivariate associations between the disorders with fixed or random effects. Sensitivity and subgroup analyzes were conducted to analyze sources of heterogeneity, and Egger's and Begg's tests combined with funnel plots were applied to assess publication bias.ResultsSummary analysis of the results of 20 studies covering 675,291 individuals showed that the bidirectional association between SNL and depression and anxiety disorders. The incidence (OR = 0.17, 95% CI: 0.09-0.28) and risk (OR = 1.43, 95% CI: 1.32-1.55) of depression and morbidity were higher in SNL patients than the general population. Elevated prevalence (OR = 0.46, 95% CI: 0.28-0.65) and risk (OR = 1.30, 95% CI: 1.11-1.48) of SNL were also observed in depressed patients. The prevalence of anxiety disorders among SNL patients was about 40% (OR = 0.40, 95% CI: 0.24%-0.57), which was associated with higher risk (OR = 1.83, 95% CI: 1.42-2.24) of development than the general population. Incidence of SNL in patients with anxiety disorders was approximately 31% (OR = 0.31, 95% CI: 0.29-0.33). Additionally, subgroup analyzes showed that the bidirectional associations between SNL, depression, and anxiety disorders was influenced by age, region, and mode of diagnosis of the disorders (SNL, depression, anxiety).ConclusionThere are bidirectional associations between SNL and depression and anxiety disorders, which was influenced by age and region and the method the disorders (SNL, depression, anxiety) were diagnosed.